An Open Label Trial to Assess Safety of Losartan for Treating Worsening Respiratory Illness in COVID-19 - Bengtson, Charles D.; Montgomery, Robert N.; Nazir, Usman; Satterwhite, Lewis; Kim, Michael D.; Bahr, Nathan C.; Castro, Mario; Baumlin, Nathalie; Salathe, Matthias (Frontiers in Medicine, 2021)
Rationale: Coronavirus disease 2019 (COVID-19) can cause disruption of the renin-angiotensin system in the lungs, possibly contributing to pulmonary capillary leakage. Thus, angiotensin receptor blockers (ARBs) may improve respiratory failure. Objective: Assess safety of losartan for use in respiratory failure related to COVID-19 (NCT04335123). Methods: Single arm, open label trial of losartan in those hospitalized with respiratory failure related to COVID-19. Oral losartan (25 mg daily for 3 days, then 50 mg) was administered from enrollment until day 14 or hospital discharge. A post-hoc external control group with patients who met all inclusion criteria was matched 1:1 to the treatment group using propensity scores for comparison. Measures: Primary outcome was cumulative incidence of any adverse events. Secondary, explorative endpoints included measures of respiratory failure, length of stay and vital status. Results: Of the 34 participants enrolled in the trial, 30 completed the study with a mean age SD of 53.8 ± 17.7 years and 17 males (57%). On losartan, 24/30 (80%) experienced an adverse event as opposed to 29/30 (97%) of controls, with a lower average number of adverse events on losartan relative to control (2.2 vs. 3.3). Using Poisson regression and controlling for age, sex, race, date of enrollment, disease severity at enrollment, and history of high-risk comorbidities, the incidence rate ratio of adverse events on losartan relative to control was 0.69 (95% CI: 0.49–0.97) Conclusions: Losartan appeared safe for COVID-19-related acute respiratory compromise. To assess true efficacy, randomized trials are needed.